Circulating cell-free long DNA fragments predict post-hepatectomy recurrence of colorectal liver metastases. Issue 1 (January 2020) - Iwai, Takuma; Yamada, Takeshi; Takahashi, Goro; Takeda, Kohki; Koizumi, Michihiro; Shinji, Seiichi; Matsuda, Akihisa; Yokoyama, Yasuyuki; Hara, Keisuke; Ueda, Kohji; Ohta, Ryo; Taniai, Nobuhiko; et al.
Abstract: Introduction: Most patients with colorectal liver metastases, who undergo hepatectomy, experience recurrence. Although the prognosis is poorer for patients with early recurrence (within 6 months after hepatectomy) compared with later recurrence, no biomarker has been identified to predict early recurrence. Minimal residual disease (MRD) in patients who undergo curative surgery is the main cause of recurrence. In cancer patients, long fragment cell-free DNA is detected, and the presence of long fragments of cell-free DNA after surgery can indicate MRD. In this study, we developed a novel biomarker to predict early recurrence of colorectal liver metastases using cell-free DNA. Materials and methods: Forty-one patients with colorectal liver metastases were enrolled. Peripheral blood samples were collected before and at 1 month after hepatectomy. Cell-free DNA was extracted from 1 ml plasma, and the long fragment/β-globin ratio, which can indicate MRD, was measured by real-time polymerase chain reaction. Results: Three of 21 patients (14.3%) with decreases in the long cell-free DNA fragment/β-globin ratio after hepatectomy developed early recurrence compared with twelve of 20 patients (60.0%) with an increased ratio ( P  = 0.002). Patients with a decreased long fragment/β-globin ratio after hepatectomy had significantly longer recurrence-free survival compared with patients with an increased ratio (366 vs 102 days, P  < 0.001). Conclusion: The cell-free DNA long fragment/β-globin ratio may serve as an effective biomarker of early recurrence in patients with colorectal liver metastases, who undergo hepatectomy.